2012
DOI: 10.1128/jvi.01073-12
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Ephemeral Fever Virus Uses a Clathrin-Mediated and Dynamin 2-Dependent Endocytosis Pathway That Requires Rab5 and Rab7 as Well as Microtubules

Abstract: The specific cell pathways involved in bovine ephemeral fever virus (BEFV) cell entry have not been determined. In this work, colocalization of the M protein of BEFV with clathrin or dynamin 2 was observed under a fluorescence microscope. To better understand BEFV entry, we carried out internalization studies with a fluorescently labeled BEFV by using a lipophilic dye, 3,30-dilinoleyloxacarbocyanine perchlorate (DiO), further suggesting that BEFV uses a clathrin-mediated endocytosis pathway. Our results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…In addition, the endosomal pathway has been shown to promote internalization and/or virus replication (60)(61)(62)(63). Indeed, entry into Rab5 ϩ early endosomes has been previously described for Uukuniemi virus, another member of the genus Phlebovirus (64).…”
Section: Sftsv Nss Sequesters Rig-i Signaling Molecules Into Nssinducmentioning
confidence: 99%
“…In addition, the endosomal pathway has been shown to promote internalization and/or virus replication (60)(61)(62)(63). Indeed, entry into Rab5 ϩ early endosomes has been previously described for Uukuniemi virus, another member of the genus Phlebovirus (64).…”
Section: Sftsv Nss Sequesters Rig-i Signaling Molecules Into Nssinducmentioning
confidence: 99%
“…It has been reported that VSV enters cells through a clathrin‐mediated and dynamin‐dependent endocytic pathway (Cureton et al ., ). More recently, we reported that BEFV uses a clathrin‐mediated and dynamin 2‐dependent endocytic pathway that requires Rab 5 and Rab 7 as well as microtubules (Cheng et al ., ); nevertheless, whether BEFV‐triggered signalling pathways regulating virus entry remain largely unknown. In the present study, experiments were performed first to assess signal pathways mediating BEFV entry and replication.…”
Section: Introductionmentioning
confidence: 99%
“…This step is regulated by Rab proteins, the small GTPases (22,23). Of these proteins, Rab5 and Rab7 play major roles in endocytic vesicle trafficking (24)(25)(26)(27)(28). Rab5 and Rab7 are involved in the life cycles of multiple viruses in the family Flaviviridae, such as hepatitis C virus (HCV) (29,30), dengue virus (DNV), and West Nile virus (WNV) (31,32).…”
mentioning
confidence: 99%